Pembacaan Kontekstual Fazlur Rahman Atas Sunah Dan Hadis (Upaya Mendialektikkan Dua Tipologi Pemikiran Tradisionalis Dan Modernis) - Roibin, Roibin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2002)
Fazlur Rahman states that Sunnah tends to be guidance not a set of rule. Thus, efforts should be done to formalize, verbalize and make it permanent in the form of Hadith text. Otherwise, Moslems will face discontinuity of history. However, the formulized Hadiths do not necessarilyÂ mean that the Hadiths become absolute. When it is so, the Hadiths were essentially reduced.